2014
DOI: 10.1007/s11745-014-3958-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compounds Affecting ABCA1 Expression and CETP Activity on the HDL Pathway Involved in Intestinal Absorption of Lutein and Zeaxanthin

Abstract: The antioxidant xanthophylls lutein and zeaxanthin are absorbed from the diet in a process involving lipoprotein formation. Selective mechanisms exist for their intestinal uptake and tissue-selective distribution, but these are poorly understood. We investigated the role of high-density lipoprotein (HDL), apolipoprotein (apo) A1 and ATP-binding cassette transporter (ABC) A1 in intestinal uptake of lutein in a human polarized intestinal cell culture and a hamster model. Animals received dietary lutein and zeaxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…The ABCA‐1/ApoA‐I complex absorbs antioxidants ( i.e lutein, zeaxanthin, etc.) which are LDL‐protecting molecules, thus contributing to the formation of nascent HDL . ABCA1/ApoA‐I activity is fundamental for the formation of the nascent HDL (pre‐β1 fractions), which are also efficient acceptors of cell cholesterol via ABCG1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ABCA‐1/ApoA‐I complex absorbs antioxidants ( i.e lutein, zeaxanthin, etc.) which are LDL‐protecting molecules, thus contributing to the formation of nascent HDL . ABCA1/ApoA‐I activity is fundamental for the formation of the nascent HDL (pre‐β1 fractions), which are also efficient acceptors of cell cholesterol via ABCG1 .…”
Section: Discussionmentioning
confidence: 99%
“…which are LDL-protecting molecules, thus contributing to the formation of nascent HDL. [34] ABCA1/ApoA-I activity is fundamental for the formation of the nascent HDL (pre-β1 fractions), which are also efficient acceptors of cell cholesterol via ABCG1. [4] In agreement with our past findings, HDL oxidation decreases HDL fluidity and concomitantly CEC.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that these experiments were performed in the absence of concomitant statin treatment. Recently, we reported [27] that dalcetrapib treatment of hamsters increased the intestinal absorption of the antioxidants lutein and zeaxanthin via an HDL pathway, which is ABCA1 and ApoA1 dependent. Simvastatin treatment decreased the expression of intestinal ABCA1, decreased lutein and zeaxanthin concentrations in plasma and liver, and abrogated the effect of dalcetrapib on lutein and zeaxanthin absorption.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that dalcetrapib (but not anacetrapib) treatment increased in vivo the intestinal uptake of two antioxidants of dietary origin-lutein and zeaxanthin (87). This process, which is like cholesterol and phospholipid efflux-an ABCA1/ApoA1 driven process-support the hypothesis that the HDL raised by dalcetrapib is functional.…”
Section: Discussionmentioning
confidence: 77%